2006
DOI: 10.1016/j.jacc.2005.11.080
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Contrast Removal System From the Coronary Sinus Using an Adsorbing Column During Coronary Angiography in a Porcine Model

Abstract: The contrast removal system from CS is effective and safe during coronary angiography in swine. This technique may be useful for preventing CIN in patients with renal insufficiency undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Future approaches include large planned studies of oral and intravenous antioxidants (including a potent oral antioxidant, deferiprone), intrarenal infusions of renal vasodilators using flow directed catheters, forced hydration with marked elevations of urine output to reduce the transit time of iodinated contrast in the renal tubules, systemic cooling, and novel, hopefully less toxic, forms of radio-opaque contrast agents. Another novel approach may involve coronary sinus withdrawal of blood and contrast after intracoronary injection, thus reducing the volume of contrast delivered downstream to the kidneys (73,74). If Advanced Algorithm for Management of Patients Receiving Iodinated Contrast Media cardiovascular procedures could be performed with no risk of AKI, it is expected that major adverse cardiac and medical complications could be appreciably reduced.…”
Section: Future Preventive Approachesmentioning
confidence: 99%
“…Future approaches include large planned studies of oral and intravenous antioxidants (including a potent oral antioxidant, deferiprone), intrarenal infusions of renal vasodilators using flow directed catheters, forced hydration with marked elevations of urine output to reduce the transit time of iodinated contrast in the renal tubules, systemic cooling, and novel, hopefully less toxic, forms of radio-opaque contrast agents. Another novel approach may involve coronary sinus withdrawal of blood and contrast after intracoronary injection, thus reducing the volume of contrast delivered downstream to the kidneys (73,74). If Advanced Algorithm for Management of Patients Receiving Iodinated Contrast Media cardiovascular procedures could be performed with no risk of AKI, it is expected that major adverse cardiac and medical complications could be appreciably reduced.…”
Section: Future Preventive Approachesmentioning
confidence: 99%
“…Future approaches include large planned studies of oral and intravenous antioxidants (including a potent oral antioxidant, deferiprone), intrarenal infusions of renal vasodilators using flow directed catheters in the procedural suite or intensive care unit, forced hydration using a balancing pump with marked elevations of urine output to reduce the transit time of iodinated contrast in the renal tubules, systemic cooling, and novel, hopefully less toxic forms of radiopaque contrast agents. Another approach may involve coronary sinus withdrawal of blood and contrast after intracoronary injection, thus reducing the volume of contrast delivered downstream to the kidneys [85, 86]. If procedures using iodinated contrast could be performed with no risk of AKI, it is expected that major medical complications and death could be appreciably reduced.…”
Section: Future Approachesmentioning
confidence: 99%
“…On the other hand, Marenzi et al [15] reported the efficacy and safety of periprocedural hemofiltration (HF). We previously reported the efficacy of a contrast removal system from the coronary sinus using an adsorbing column during CAG [16]. This suggests the possibility of blood suction from the right atrium for hemodiafiltration (HDF).…”
Section: Introductionmentioning
confidence: 99%